Pengaruh Model Pembelajaran Kuantum Berbantuan Simulasi PHET Terhadap Penguasaan Konsep Fisika Peserta Didik - Siti Aminah; Aris Doyan; Hikmawati Hikmawati (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2020)
This research aim to into examine the effect of quantum learning model assisted phet simulation  for students physic concept mastery. This type of research is quasi experiment with untreated control group design with pretest and posttest. The research popuplation was all students os XI MIA MAN 2 Mataram. Sampling technique of this research use cluster random sampling so that there are two classes that is XI MIA 5 as the experimental class and XI MIA 6 as the control class. Type test used 20 choice question for concept mastery. The posttest mean value for concept mastery in experimental class and control class is 54,29 and 44,54. Hypothesis testing of this research is MANOVA. The resul of MANOVA test show a significant 0,043 so H0 is rejected and Ha is accepted. The conclution of this research is there is the effect of quantum learning model assisted phet simulation for students physic concept mastery.